Analisis Potensi Museum Batubara PT. Bukit Asam Tanjung Enim Sebagai Sumber Belajar Sejarah - Radiallah, Abdan; Wijaya, Daya Negri; Hudiyanto, R. Reza; Widiadi, Aditya Nugroho (Cetta: Jurnal Ilmu Pendidikan, 2024)
History learning has an ongoing problem because of the assumption that history is just memorizing an event, so that learning is less meaningful. In fact, learning history provides new understanding and knowledge so that students are able to criticize things wisely. The phenomenon in the field is found that students are given learning to know other regions but do not study their own regions. From this problem, the researcher saw that there was potential from the PT Bukit Asam Coal Museum in Tanjung Enim to be an interesting object as a meaningful history learning resource for students. The purpose of this study examines how the potential of the PT Bukit Asam Coal Museum in Tanjung Enim as an appropriate and effective history learning resource. This research is a qualitative research using descriptive analysis techniques with literature review. The results of the research based on literature review and interviews conducted, researchers saw quite a lot of schools and public visitors who made field trips to the museum, meaning that this field trip-based history learning strategy is quite potential and effective to be applied to students. The field trip strategy helps students form a certain picture of the object being studied. Learning outside the classroom is one of the most effective learning strategies that gives students the freedom to develop and explore what they learn directly. Through field trip activities, students seem to be entertained because they can see and learn directly through the museum.